Estudio de prefactibilidad para la instalación de una planta productora de cerveza artesanal de camu camu - Bouroncle Alarcon, Juan Diego (2021)
The purpose of this project will be to evaluate the commercial, technical, financial, economic and social viability of the installation of a camu camu craft beer production plant destined for modern Lima, which will consist of water, malted barley, hops, yeast and camu camu and whose added value is that it will have a lower degree of alcohol for those who seek this type of characteristics in a fruity beer. It is considered a contribution in the category of craft beers since the aroma and flavor that it will present will be innovative in the market because the exotic fruit it will contain is pleasant to the Peruvian palate. An annual demand of 122,723 bottles is projected for the last year of the project and will be commercialized through the on trade and off trade channels. The target audience is comprised of modern Lima that encompasses 12 districts, people over 18 years of age from socioeconomic levels a, b and c. The plant will be located in the metropolitan city of Lima. The production process consists of milling the malt, treating the water, heating, mashing, boiling, centrifuging, pre-filtering, cooling and fermenting the wort, filtering, aerating and bottling.